Typifications in Drimia with notes on the identity of D. wightii (Asparagaceae, Scilloideae) - Yadav, Pradnya B.; Lekhak, Manoj M.; Yadav, Shrirang R. (Phytotaxa, 2016)
Three binomials, viz. Scilla coromandeliana, Drimia razii and D. wightii, are typified in accordance with the International Code of Nomenclature for algae, fungi, and plants (ICN). Further, notes on the identity of Drimia wightii, a synanthous species, are also provided.